Electron‐Beam‐Induced Deposition of Bimetallic Nanostructures from Bulk Liquids1. Issue 31 (20th June 2013) - Bresin, Matthew; Chamberlain, Adam; Donev, Eugenii U.; Samantaray, Chandan B.; Schardien, Gregory S.; Hastings, J. Todd
<x xml:space="preserve">Abstract</x> Bimetallic deposits: Liquid‐phase electron‐beam‐induced deposition is shown to result in bimetallic deposits with predictable final compositions. The compositions were predicted by the first‐order rates of the reaction between solvated electrons and metal ionic complexes. AuAg and AuPt nanoparticles are shown with diameters typically less than 100 nm and high purity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>